The Effect of Ice Breaking in Increasing Student Learning Motivation in Elementary Schools - Idzil Ghasyiyah Andesti; Sahrun Nisa; Ari Suriani (MANDALIKA : Journal of Social Science, 2025)
This study aims to analyze the effect of using ice breaking in increasing students' learning motivation in elementary schools. The research method used is a literature study with a qualitative approach. The analysis results show that the application of ice breaking in learning in elementary schools has a positive and significant impact on students' learning motivation. Ice breaking can make students more active, enthusiastic, and focused on learning, thus improving their learning outcomes. Learning motivation is an important factor in learning, as it can affect various abilities and student learning outcomes. Therefore, teachers need to understand and foster motivation for learning in students using ice breaking in the learning process so that students can achieve success in learning.